2020
DOI: 10.1186/s13071-020-04251-7
|View full text |Cite
|
Sign up to set email alerts
|

TgROP18 targets IL20RB for host-defense-related-STAT3 activation during Toxoplasma gondii infection

Abstract: Background: Toxoplasma gondii is an opportunistic protozoan infecting almost one-third of the world's population. Toxoplasma gondii rhoptry protein 18 (TgROP18) is a key virulence factor determining the parasite's acute virulence and is secreted into host cells during infection. We previously identified the interaction of TgROP18 and host cell immune-related receptor protein IL20RB, and observed the activation of STAT3 in human keratinocytes (HaCaT) cells infected by the rop16 knockout RH strain, though TgROP1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Studies have shown that T. gondii infection upregulated p-STAT3(705) expression in bone marrow-derived macrophages [ 48 ] and the A549 cell line [ 49 ]. For p-STAT3(727), however, no significant differences were found after RH T. gondii infection in human HaCaT cells [ 50 ]. To date, no studies about p-STAT3(727) expression have been reported in human dDCs with T. gondii infection.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that T. gondii infection upregulated p-STAT3(705) expression in bone marrow-derived macrophages [ 48 ] and the A549 cell line [ 49 ]. For p-STAT3(727), however, no significant differences were found after RH T. gondii infection in human HaCaT cells [ 50 ]. To date, no studies about p-STAT3(727) expression have been reported in human dDCs with T. gondii infection.…”
Section: Discussionmentioning
confidence: 99%
“…This pathway is identified to have the ability to trigger epidermal hyperplasia, and skin inflammation thereby is supposed to be related with the pathogenesis of chronic inflammation and autoimmune diseases [ 15 ]. Although IL20RB was initially found to be involved in many nonmalignant diseases, such as psoriasis [ 16 ], rheumatoid arthritis [ 17 ], vitiligo [ 18 ], ulcerative colitis [ 19 ], glaucoma [ 20 ], asthma [ 21 ], endometriosis [ 22 ], and chronic rhinosinusitis [ 23 ] as well as infectious diseases [ 24 ], novel discoveries indicate IL20RB could also play an important role in malignant diseases. Recently, increasing evidence supports IL20RB also plays a vital role in human cancers such as colorectal adenocarcinoma [ 25 ], breast cancer [ 26 ], and esophageal carcinoma [ 27 ], while its role in ccRCC still remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The isolated exosomes and the transfected cells were collected and lysed using lysis buffer (Beyotime Biotechnology, Shanghai, China), total proteins were loaded for sodium dodecyl sulphate–polyacrylamide gel electrophoresis (SDS-PAGE), and WB was performed as described previously [ 29 ]. The following primary antibodies were used: CD9 rabbit monoclonal antibody (mAb; 1:1000), TSG101 rabbit mAb (1:1000), HSP70 rabbit mAb (1:1000), iNOS rabbit mAb (1:1000), p65 rabbit mAb (1:1000), and SOCS1 rabbit mAb (1:1000) purchased from Abcam (MA, USA); GAPDH mouse mAb (1:1000), phosphorylated IκB alpha (Ser32/Ser36) mouse mAb (1:1000), and phosphorylated NF-κB p65 (S536) mouse mAb (1:1000) purchased from Affinity Biosciences (OH, USA); and IKBα rabbit mAb (1:1000) purchased from GeneTex (Santa Cruz, CA, USA).…”
Section: Methodsmentioning
confidence: 99%